Tumor necrosis factor enhances the sleep‐like state and electrical stimulation induces a wake‐like state in co‐cultures of neurons and glia. (28th June 2015) - Jewett, Kathryn A.; Taishi, Ping; Sengupta, Parijat; Roy, Sandip; Davis, Christopher J.; Krueger, James M.
Abstract We characterise sleep‐like states in cultured neurons and glia during development in vitro as well as after electrical stimulation, the addition of tumor necrosis factor alpha (TNF), and the combination of TNF plus electrical stimulation. We also characterise optogenetic stimulation‐induced ATP release and neuronal interleukin‐1 and TNF expression in vitro demonstrating the activity dependence of these putative sleep‐regulatory substances. Action potential (AP) burstiness, expressed as the burstiness index (BI), synchronization of slow electrical potentials between recording electrodes (SYN), and slow wave (SW) power (0.25–3.75 Hz) determined using fast Fourier analyses emerged as network properties, maturing after 2 weeks in culture. Homologous in vivo measures are used to characterise sleep. Electrical stimulation reduced the BI, SYN and SW power values during and/or after the stimulus period. One day later, homeostasis was evident from rebounds of SYN and SW power values to above baseline levels; the magnitude of the rebound was stimulus pattern‐dependent. The addition of TNF enhanced BI, SYN and SW power values, suggesting the induction of a deeper sleep‐like state. Electrical stimulation reversed these TNF effects, suggesting the network state was more wake‐like. The day after TNF plus electrical stimulation, the changes in SYN and SW power values were dependent upon the stimulus patterns the cells received the day before. We conclude that sleep and wake states in cultured in vitro networks can be controlled and they share molecular regulatory mechanisms with local in vivo networks. Further, sleep is an activity‐dependent emergent local network property.